1994
DOI: 10.1088/0953-4075/27/6/020
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted elastic electron-atom collisions: low electron energy and small scattering angle

Abstract: The authors report experimental measurements of electron spectra resulting from the scattering of low energy (6.2-32 eV) electrons by helium atoms through an angle of 9 degrees in the presence of a high intensity ( approximately 108 W cm-2)CO2 laser. The intensities of the additional peaks caused by the presence of the laser which occur separated from the elastic scattering peak by multiples of the photon energy are much greater than expected on the basis of calculations, using the Kroll-Watson approximation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 30 publications
5
62
0
Order By: Relevance
“…(5) shows that this occurs for small x, and, since x ∝ǫ·Q, there are two simple possible experimental ways of achieving this. Thus for the experiments of Wallbank and Holmes referred to above, the 9 • scattering experiment [4,11] corresponds to small Q (andǫ almost perpendicular to Q), and the other experiment [12] hasǫ · Q = 0. Figure 2 shows the two-photon to one-photon free-free cross-section ratio at 300 eV incident energy as a function of laser intensity.…”
Section: Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…(5) shows that this occurs for small x, and, since x ∝ǫ·Q, there are two simple possible experimental ways of achieving this. Thus for the experiments of Wallbank and Holmes referred to above, the 9 • scattering experiment [4,11] corresponds to small Q (andǫ almost perpendicular to Q), and the other experiment [12] hasǫ · Q = 0. Figure 2 shows the two-photon to one-photon free-free cross-section ratio at 300 eV incident energy as a function of laser intensity.…”
Section: Theorymentioning
confidence: 97%
“…The neglect of the laser-atom interaction can be investigated by experiments carried out with high laser power, but under conditions where the Kroll-Watson approximation predicts very small, or indeed vanishing, free-free cross sections. Wallbank and Holmes carried out a free-free experiment for electrons scattered through 9 • , for which the Kroll-Watson approximation predicts a small cross-section [4,11]. It was found that the Kroll-Watson approximation underestimated the free-free cross sections by orders of magnitude.…”
mentioning
confidence: 99%
“…As recently the prospects of combining static and time-dependent fields to lower the critical field have triggered new discussions [2], it seems worthwhile to explore if Hund's conjecture to map an intrinsic quantum field theoretical process onto a quantum mechanical scattering problem could even be generalized to those external force fields that in addition to a spatial dependence have also a temporal dependence. If this is possible and the vacuum's decay rate can be calculated from the laser-assisted scattering system, then this quantum field theoretical process should also be 4/26/2018 amenable to powerful solution techniques, such as the Kroll-Watson formula [14] and its generalizations [15][16][17][18][19][20] and other techniques that so successfully described laser-assisted scattering experiments [21][22][23].…”
mentioning
confidence: 99%
“…Similar experiments by Weingartshofer et al [10] observed the absorption and emission of up to three 0.117 eV photons during e-Ar elastic scattering in the presence of a pulsed CO 2 laser. Wallbank and Holmes [11][12][13] later carried out similar experiments using a pulsed CO 2 laser and helium and argon targets; they reported the absorption and emission of up to five 0.117 eV photons. Mason and Newell [14] carried out the first experiment on electron impact excitation in the presence of a CO 2 laser field (simultaneous electronphoton excitation, or SEPE), and Luan et al [15] investigated SEPE in He using a Nd:YAG laser which produces photons of energy 1.17 eV, ten times the CO 2 laser energy.…”
Section: Introductionmentioning
confidence: 95%